Open Educational Resources (OERs) Development in Nigeria: Determining Task Technology Fit (TTF) Impact on Faculty Usage, Satisfaction and Performance - Osang, F.B. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
Open educational resources (OER) are gaining grounds globally. However, different regions face different obstacles to OER adoption, policies and experiences. Unfortunately, Africa has continued to trail behind the rest of the world in the adoption of OERs. A number of factors have been adduced from literature ranging from lack of awareness; absence of policies, infrastructural deficits among others with total absence of literature on the fit of the existing technologies being used and how these technologies fit affects utilization, satisfaction and performance impacts. This work adopted the TUSPEM model as a theoretical framework to assess the causal relationship among five constructs of Task Technology Fit, social norms, utilization, satisfaction and performance impacts. Through a quantitative research approach, snowballing sampling was adopted to identify 123 respondents from a Nigerian University. Smart PLS was used to analyze the dataset. Although the results had strong support for relationships between TTF, satisfaction, the result showed a stronger relationship from post usage satisfaction to performance than TTF to performance. It implies that in a voluntary usage environment, TTF and user satisfaction is critical if performance using any information system is to be achieved.